1997
DOI: 10.1046/j.1365-2141.1997.302677.x
|View full text |Cite
|
Sign up to set email alerts
|

Collection of peripheral blood stem cells from normal donors 60 years of age or older

Abstract: Summary. We report 14 normal peripheral blood stem cell (PBSC) donors у 60 years of age who had cytokine mobilization followed by PBSC apheresis for allogeneic transplantation. Mobilization was achieved with filgrastim (6 mg/kg twice daily). Their median age was 63·5 years (range 60-77), and 43% had a positive medical history, mainly hypertension and/or cardiac problems. Their median pre-apheresis leucocyte count (× 10 9

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 8 publications
1
26
0
Order By: Relevance
“…Several small-to moderate-sized experiences have been published describing PBSC donor outcomes, focusing mainly on related donors. 4,7,10,11,[15][16][17] Short-term toxicities associated with PBSC donation reported previously generally occurred because of either (1) For personal use only. on May 7, 2018.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several small-to moderate-sized experiences have been published describing PBSC donor outcomes, focusing mainly on related donors. 4,7,10,11,[15][16][17] Short-term toxicities associated with PBSC donation reported previously generally occurred because of either (1) For personal use only. on May 7, 2018.…”
Section: Discussionmentioning
confidence: 99%
“…The practice initially involved related donors, but in more recent years this method of collection has been extended to healthy unrelated donors. Although several studies have addressed safety considerations of the procedure for small cohorts of related donors, [1][2][3][4][5][6][7][8][9][10] published unrelated donor safety experience is minimal, [11][12][13] and large, comprehensive studies of PBSC donor safety in healthy unrelated donors have not been published. In addition, previous studies have not used standardized toxicity scales, making it difficult to compare the studies with each other and giving an incomplete understanding of the donor experience.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, evidence for stem/progenitor cell pool depletion in the human body with aging includes peripheral blood stem cells [8,9], satellite cells of skeletal muscle [10], and putative stem cells of the epidermal compartment of the skin [11]. Interestingly, in a retrospective analysis of >6,900 bone marrow transplantations conducted by the National Marrow Donor Program, age was the only donor trait significantly associated with recipient survival [12].…”
Section: Introductionmentioning
confidence: 99%
“…It has been repeatedly observed that older donors tend to produce a lower CD34+ cell number requiring frequently more than one leukopheresis as compared to younger donors [8][9][10][11]. Repeated leukopheresis can pose a donor at increased risks, in particular to deeper and longer thrombocytopenia [12].…”
Section: Donor Eligibilitymentioning
confidence: 99%